Asian Winter Monsoon Imprint on the Water Column Structure at the Northern South China Sea Coast - Zhang, Yancheng; Zhu, Kai; Huang, Chao; Kong, Deming; He, Yuxin; Wang, Huanye; Liu, Weiguo; Xie, Zhouqing; Wei, Gangjian; Liu, Zhonghui (Frontiers in Earth Science, 2021)
Coastal regions of the northern South China Sea (SCS) strongly interact with the Asian monsoon circulation (AMC). Thus, variations of sea surface temperature (SST) here are newly suggested to document AMC changes in an effective manner, but additional physical parameters of oceanic conditions, probably also in relation to the AMC system, remain poorly understood. In this study, we analysed glycerol dialkyl glycerol tetraethers (GDGTs) from a well-dated sediment core YJ, retrieved at the northern SCS coast, to further scrutinize the intrinsic response of water column to winter AMC strength. It shows that, within the time frame of past ~1,000 years, the tetraether index of lipids with 86 carbon atoms (TEX86) and published alkenone (Uk'37) temperature records together confirm a reduced thermal gradient during the Little Ice Age (LIA), in comparison to that during the Medieval Climate Anomaly (MCA). Considering concurrent variations of the branched and isoprenoid tetraether (BIT) and ratio of archaeol to caldarchaeol (ACE), e.g., with decreased values (< ~0.3) for the former and relatively high values for the latter at the LIA, indicative of stratification and salinity changes respectively, these multiple lines of evidence thereby call for well-mixing of onsite water at site YJ correspondingly. Our results suggest that winter AMC strength is a critical factor for mixing subsurface waters and modifying thermal/saline conditions at the northern SCS coasts through the last millennium and also, perhaps, on longer timescales.